Avaliação dos parâmetros clínicos periodontais, da qualidade de vida e da experiência de dor, medo e ansiedade em indivíduos submetidos às técnicas de raspagem e alisamento radicular por quadrante e ao protocolo de One-stage Full-mouth Disinfection no tratamento de periodontite: um ensaio clínico randomizado controlado - Camila de Carvalho Santuchi (2014)
The aim of this blinded randomized controlled clinical trial was to evaluate and compare the effect of two types of non-surgical periodontal therapy, scaling and root planing per quadrant (SRP) and one-stage full-mouth disinfection (FMD) in periodontal clinical parameters, quality of life, fear, anxiety and pain experience in patients with chronic periodontitis. The instruments Oral Impacts on Daily Performances (OIDP), Oral Health and Quality of Life (OHQoL) Dental Fear Survey (DFS), Dental Anxiety Scale (DAS) and Visual Analogue Scale (VAS) were applied in 78 subjects divided into 2 treatment groups: SRP (n=37) and FDM (n=41). The periodontal clinical parameters: probing depth (PD), clinical attachment level (CAL), plaque index (PI), gingival index (GI) and % of diseased sites (PD4mm and CAL3mm), were collected. Assessments were performed at baseline or T0 (periodontal clinical parameters, DAS and DFS), 30 days after periodontal therapy or T1 (OIDP and OHQoL) and 180 days after periodontal therapy or T2 (periodontal clinical parameters, OHQoL, OIDP, DAS and DFS). The application of VAS was performed immediately after completion of therapy. For statistical analysis, the Kruskal-Wallis test, Pearson correlation, Wilcoxon test were performed. Besides a Cluster Analysis were perormed in order to determine distinct profiles of individuals, based on questionnaires OHQoL, OIDP, DAS and DFS. Analyses were performed using SPSS 17.0 software and the results were considered significant for p0,005. It was observed a significant negative correlation between OHQOL scores and CAL (-0.35), PI (-0.23) and GI (-0.27) and a significant positive correlation between OIDP and CAL (0.41) and % of diseased sites (0.23), in T0/T1. The same significant correlation was maintained in T2, except for the periodontal clinical parameter PI. Cluster analysis identified two clusters: A (n = 33) greater impact/worse quality of life, greater fear and anxiety, and B (n = 42) lower impact/better quality of life, less fear and anxiety. There was a significant reduction in all periodontal clinical parameters comparing the results before and after treatment and a negative association between fear and anxiety, and CAL, PI and GI. Both groups showed a decline in fear and anxiety after treatment: FMD (p=0.019) and SRP (p=0.043). Both groups showed similar mean for pain scale: FMD (2.6 ± 1.9) and RAR-Q (2.7 ± 2.0) (p = 0.930). We conclude that individuals treated by SRP and the FMD showed an improvement in all periodontal clinical parameters and quality of life, with no significant differences between them. There were no significant differences between treatment by SRP and FMD in the scores of pain, the same occurred for anxiety and fear in T0/T1 and T2.